IMPLEMENTATION OF PROBLEM SOLVING METHODS TO IMPROVE LEARNING RESULTS IN USE OF NATURAL RESOURCES FOR STUDENTS OF CLASS IV UPT SD NEGERI 1 PUJODADI: Indonesia - Rizki Nur Fatoni; Muhtarom Muhtarom; Abdul Hamid (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Abstract This classroom action research aims to improve student learning outcomes in social studies subjects, especially in the topic of utilization of natural resources, through the application of problem solving methods in class IV UPT SD Negeri 1 Pujodadi in the 2022/2023 academic year. The method used in this study is descriptive quantitative, because the data produced will be in the form of written or oral descriptions and involves observing behavior from various sources of information. Quantitative data is also used to support the success of the learning process. The research subjects consisted of 18 grade IV students, with details of 8 male students and 10 female students. The implementation of this research consisted of two cycles, each with four stages, namely planning, implementing, observing, and reflecting The percentage of students reached 40% of the learning outcomes in Cycle I. This shows that students still need to improve their learning. However, in Cycle II there was an increase in learning activity by 100%, this indicates that the class average in Cycle II increased as a result of increased student interest and understanding of the learning process. There is an increase in student learning outcomes in social studies subjects regarding the utilization of natural resources can be seen from the data showing this increase. Keywords: Learning Outcomes, Problem Solving Method